Integrated transcriptome and metabolome provide insights into flavonoid biosynthesis in 'P113', a new purple tea of Camellia tachangensis - Fang Li; Xinyue Deng; Zheng Huang; Zhifei Zhao; Caiyun Li; Qinfei Song; Yingqin He; Suzhen Niu (Beverage Plant Research)
Plants typically exhibit the purple phenomenon as a result of an increase in flavonoids and anthocyanins. A new tea germplasm 'P113' was recently selected from Camellia tachangensis, which is purple in tender shoots. In the present study, integrated transcriptome and metabolome were used to analyze the flavonoid metabolite components and the genes involved in flavonoid biosynthesis in 'P113'. A total of 86 flavonoid metabolites were identified, including 70 significantly differential metabolites (p < 0.05) and they were enriched to the three metabolic pathways of ko00941, ko00942 and ko00944 through KEGG pathway analysis. A total of 136 flavonoid involved genes were obtained from transcriptomic study, of which 53 were significantly differentially expressed in developmental shoots. The correlation between metabolite profiling and transcriptome, transcriptome and protein interactions suggested that transcription factor MYB12 and glycosyltransferase UGT78D2 had a good facilitation on purple tender shoots. The metabolic pathways and potential genes that underlie the coloration of the shoots in 'P113' are clarified in this study. It also lays the groundwork for identifying potential genes involved in color variation and offers a theoretical framework for the creation and use of distinctive genetic resources and the breeding of new cultivars.